PERSEPSI MAHASISWA TERHADAP PENGGUNAAN APLIKASI ZOOM DALAM PERKULIAHAN KIMIA DASAR SAAT PANDEMI COVID-19 - Eliyarti Eliyarti; Chichi Rahayu (Justek : Jurnal Sains dan Teknologi, 2022)
Abstract:  The COVID-19 pandemic has had an impact on education policy in Indonesia. Learning is carried out from home (learning from home) replacing the face-to-face process in class. The use of technology is the basis so that online learning can be realized. The Zoom application is one of the technologies widely used in lectures during the Covid-19 pandemic. This type of research is quantitative descriptive which aims to describe student perceptions of the use of the zoom application in Basic Chemistry lectures during the covid-19 pandemic. The sample of this study was the first-level students of the Faculty of Engineering and Planning, Ekasakti University in the Basic Chemistry lectures in the odd semester 2020/2021 totaling 80 people who were selected using a simple random sampling technique. The data collection technique used a non-test technique in the form of a questionnaire. Based on the results of the study, it was found that students who gave a positive response to the use of the Zoom application were more than those who gave a negative response. Overall, the average percentage of students who gave a positive response was 67% in the sufficient category, while the average percentage of students who gave a negative response was 33% in the very poor category. This shows that the use of the Zoom application in Basic Chemistry lectures is able to support lecture activities. The use of the Zoom application helps students be more motivated to attend lectures during the COVID-19 pandemic.Abstrak: Pandemi COVID-19 memberikan dampak pada kebijakan bidang pendidikan di Indonesia. Pembelajaran dilaksanakan dari rumah (learning from home) menggantikan proses tatap muka di kelas. Penggunaan teknologi menjadi sandaran agar pembelajaran secara daring dapat direalisasi. Aplikasi Zoom merupakan salah satu teknologi yang banyak digunakan dalam perkuliahan saat pandemi Covid-19. Jenis penelitian  ini  deksriptif  kuantitatif  yang  bertujuan  untuk mendeskripsikan  persepsi mahasiswa terhadap penggunaan aplikasi zoom dalam perkuliahan Kimia Dasar saat pandemi covid-19. Sampel penelitian ini mahasiswa tingkat I Fakultas Teknik dan Perencanaan Universitas Ekasakti dalam perkuliahan Kimia Dasar semester ganjil 2020/2021 berjumlah 80 orang yang dipilih dengan teknik simple random sampling. Teknik pengumpulan data digunakan teknik non tes berupa kuisioner. Berdasarkan hasil penelitian diperoleh bahwa mahasiswa yang memberikan respon positif terhadap penggunaan aplikasi Zoom lebih banyak daripada yang memberikan respon negatif.  Secara keseluruhan rata-rata persentase mahasiswa yang memberikan respon positif sebesar 67% dengan kategori cukup, sedangkan rata-rata persentase mahasiswa yang memberikan respon negatif sebesar 33% dengan kategori kurang sekali. Hal ini menunjukan penggunaan aplikasi Zoom dalam perkuliahan Kimia Dasar mampu menunjang kegiatan perkuliahan. Penggunaan aplikasi Zoom membantu mahasiswa lebih termotivasi mengikuti perkuliahan saat pandemi COVID-19